La cromoterapia en la concentración de los estudiantes del Instituto Misael Acosta Solís de la ciudad de Riobamba - Gavin Quishpe, Masherlyn Elizabeth (2022)
ABSTRACT: He teaching-learning process at all levels requires a harmonious interaction between its actors: teachers, students and the learning environment. In the particular case of students, the scientific literature determines a close relationship between the psychological processes of attention and concentration. It is that attention acts as a vertical mechanism, controls and facilitates concentration, as well as the activation and functioning of these cognitive processes. In the investigated environment, the students of the Misael Acosta Solís Institute face long hours of study, which are completed after completing a work week. In the cited context, the investigated subjects demonstrated injuries inherent to: short attention span, high levels of distraction, limited ability to complete tasks in the established times, low levels of participation in class, effort, to attend and even require verbal instigation from the teacher. teacher to serve. The selected institution trains third-level professionals in Naturopathy; Among the therapies studied is chromotherapy, in which colors are used from a holistic approach to influence psychological and cognitive processes. For this reason, the research set as an objective: to establish Chromotherapy as an alternative therapy to improve the concentration of students. An integrative or mixed approach was adopted for its development. A Descriptive scope is declared, and two types according to the Design: pre-experimental in the quantitative part and Narrative in the qualitative part. The main result is the basis for the use of colors: yellow, indigo blue and green to improve attention-concentration levels and improve emotional and energetic balance in the applied population. Keywords: chromotherapy, color, attention, concentration